2016
DOI: 10.1111/ced.12798
|View full text |Cite
|
Sign up to set email alerts
|

Agminated cellular blue naevi of the penis: dermoscopic, confocal and histopathological correlation of two cases

Abstract: Blue naevi may present rarely as multiple lesions grouped in a circumscribed area, described as agminated blue naevi. This clinical presentation may mimic metastatic malignant melanoma. We present two cases of agminated cellular blue naevi of the penis, with dermoscopy, reflectance confocal microscopy and histopathological correlation. Dermoscopy of the area showed multiple grouped lesions of homogeneous dark-brown to blue colour. Using reflectance confocal microscopy, focusing on the bluish areas, predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The aggregation of melanocytes around appendages and neurovascular bundles is also commonly seen in BN. In our case, we found diffuse dermal melanocytosis, without the characteristic dendritic melanocytes of a single BN, within the dermis, which is consistent with findings reported in some of the previous cases of ABN …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The aggregation of melanocytes around appendages and neurovascular bundles is also commonly seen in BN. In our case, we found diffuse dermal melanocytosis, without the characteristic dendritic melanocytes of a single BN, within the dermis, which is consistent with findings reported in some of the previous cases of ABN …”
Section: Discussionsupporting
confidence: 92%
“…ABN is a rare entity that clinically may be similar in appearance to nevus spilus or juvenile melanoma, although the histology is usually consistent with common BN . Lesions most commonly occur on the limbs, although other locations such as the temples have also been described . Upshaw and colleagues reported the first case of a PTBN on the thorax of a 9‐year‐old boy .…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we suggest that if multiple eruptive pigmented lesions resembling BN are present, a biopsy should always be performed for a differential diagnosis with malignant or metastatic melanoma [ 1,3,[8][9][10][11] .…”
Section: Discussionmentioning
confidence: 89%
“…Eruptive blue nevi (EBN) have rarely been described [ 2,[5][6][7][8][9][10][11] . De Giorgi and colleagues [ 1 ] reported a case of EBN of the penis in an adult patient.…”
Section: Discussionmentioning
confidence: 99%
“…3 Since then, over 30 cases have been reported in the literature (Supporting Information Table S1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Unlike sporadic or common BN, which have a clinical predilection for certain anatomic sites, agminated BN present equally on the trunk, extremities, and head/neck. A review of the 31 cases published since 1990 showed that 9 were present on the extremities, 10 on the head and neck, 10 on the trunk, and 2 on the genitals (Supporting Information Table S1).…”
Section: Discussionmentioning
confidence: 99%